The Philadelphia Irish : nation, culture, and the rise of a Gaelic public sphere - Mullan, Michael L. (Michael Leigh) (Rutgers University Press, 2021)
"This monograph describes the flowering of the Irish American community and the 1890s growth of a Gaelic public sphere in Philadelphia, a movement inspired by the cultural awakening in native Ireland, transplanted and acted upon in Philadelphia's robust Irish community. The Philadelphia Irish embraced this export of cultural nationalism, reveled in Gaelic symbols, and endorsed the Gaelic language, political nationalism, Celtic paramilitarism, Gaelic sport and a broad ethnic culture. Using Jurgen Habermas's concept of a public sphere the author reveals how the Irish constructed a plebian "counter" public of Gaelic meaning through various mechanisms of communication, the ethnic press, the meeting rooms of Irish societies, the consumption of circulating pamphlets, oratory, songs, ballads, poems, and conversation. Settled in working class neighborhoods of vast spatial separation in an industrial city, the Irish resisted a parochialism identified with neighborhood and instead extended themselves to construct a vibrant, culturally engaged network of Irish rebirth in Philadelphia, a public of Gaelic meaning"--